Factors Influencing the Bacterial Bioremediation of Hydrocarbon Contaminants in the Soil: Mechanisms and Impacts. (15th November 2021) - Kebede, Gessesse; Tafese, Tekle; Abda, Ebrahim M.; Kamaraj, M.; Assefa, Fassil
Abstract : The discharge of hydrocarbons and their derivatives to environments due to human and/or natural activities cause environmental pollution (soil, water, and air) and affect the natural functioning of an ecosystem. To minimize or eradicate environmental pollution by hydrocarbon contaminants, studies showed strategies including physical, chemical, and biological approaches. Among those strategies, the use of biological techniques (especially bacterial biodegradation) is critically important to remove hydrocarbon contaminants. The current review discusses the insights of major factors that enhance or hinder the bacterial bioremediation of hydrocarbon contaminants (aliphatic, aromatic, and polyaromatic hydrocarbons) in the soil. The key factors limiting the overall hydrocarbon biodegradation are generally categorized as biotic factors and abiotic factors. Among various environmental factors, temperature range from 30 to 40°C, pH range from 5 to 8, moisture availability range from 30 to 90%, carbon/nitrogen/phosphorous (C/N/P; 100:20:1) ratio, and 10–40% of oxygen for aerobic degradation are the key factors that show positive correlation for greatest hydrocarbon biodegradation rate by altering the activities of the microbial and degradative enzymes in soil. In addition, the formation of biofilm and production of biosurfactants in hydrocarbon-polluted soil environments increase microbial adaptation to low bioavailability of hydrophobic compounds, and genes that encode for hydrocarbon degradative enzymes are critical for the potential of microbes to bioremediate soils contaminated with hydrocarbon pollutants. Therefore, this review works on the identification of factors for effective hydrocarbon biodegradation, understanding, and optimization of those factors that are essential and critical.